Impact of security dilemma on Antarctica’s militarization - Ferhat Kökyay (Polish Polar Research, 2022)
In addition to establishing an exclusive governance system in a vast area of the earth, The Antarctic Treaty is of great importance also in terms of aiming to keep a region away from military activities. In order to carry Antarctica’s dedication to peace and science to future generations, it is necessary to avoid the militarization of the Continent. However, factors such as the ever-growing need for the Continent’s resources, increasing human activities in the Continent due to global warming, and the advancing use of dual-use scientific/military equipment due to technological developments pose a danger as the militarization of the Continent and the Southern Ocean. In this study, the risk of the recent activities of the parties to create a security dilemma and the potential of the security dilemma to increase the Continent’s militarization are analysed.